Malta : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, Corporate Governance, and Payment Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The report provides the details of the Malta Financial Stability Assessment (MFSA). It defines its roles, responsibilities, and objectives for financial policies. It reviews the reports on the observance of standards and codes on monetary and financial policy transparency, banking supervision, securities regulation, insurance regulation, corporate governance, and payment systems. It assesses the macroeconomic environment and risks, soundness and vulnerabilities of the financial system, and also provides recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet